A human-centered agenda for multifunctional landscapes research - Rietveld, Anne; Garner, Elizabeth; Bryan, Elizabeth; Elias, Marlene; Verma, Benu; Moreno, Manuel (CGIAR System Organization, 2025)
Gender and other overlapping social identities shape the way people interact with the environment, as well as their perceptions of and responses to environmental change. Research on multifunctional landscapes (MFL) should, therefore, focus on humans to understand how their identities and behaviors interact with landscapes to shape resilience and sustainability. This understanding will ensure that outcomes are equitably delivered and enjoyed. Gender equality and social inclusion (GESI) have intrinsic value. GESI foster lasting achievements in terms of environmental sustainability and human well-being. Agroecological solutions must move beyond mere technical and development objectives, to adopt a human-centered approach. This focusses on local landscape actors, prioritizing their needs, and concerns in agri-food systems. Special attention is paid to women, youth and indigenous peoples, who often face multiple, intersecting forms of marginalization. MFLs comprise a mosaic of land uses that fulfill diverse needs beyond farming. These spaces enshrine diverse environmental, social, spiritual, economic and cultural values. To be considered sustainable and desirable places to live and work, MFLs must respond to the interests of multiple actors (Sunderland et al., 2014). This brief proposes a participatory action research agenda to place social inclusion, justice, and gender equality at the heart of landscape research. It supports ecological and social movements (e.g., agroecology, food sovereignty, women’s and youth’s movements) and other approaches that value nature and human development, recognizing the complexity and interdependence of human-ecological systems at a landscape level.